Pengaruh Persepsi Mahasiswa Tentang Profesi Guru dan Lingkungan Keluarga Terhadap Miinat Menjadi Guru - Shinta Haryawan; Bustari Muchtar; Rita Syofyan (Jurnal Ecogen, 2019)
The purpose of this research was to determine 1) The influence students perception about teacher profession of interest to become a teacher. 2) The influence family environment of interest become a teacher. 3) The influnce of students perception about teacher profession and family environment of interest to become a teacher. This type of research is descriptive and associative research. The population of this study is all students from economic education  padang state university in 2014, amount of the population is 88 people. The sampling technique of data collection is done by Total Sampling with amount of sample is 82 people because the  7 people have finished their studies. The data used are primary and secondary data.  This research had two categories of variable The first was the independent variable, the paerceptions of students about the teaching prefession .  The first was the independent variable, the perceptions of students about the teaching profession and family environment.  The second dependent variable, namely interests become a teacher. The analytical  method used is multiple regression analysis. The result show that. 1) Student perception about teacher profession significant effect to interest become a teacher. 2) Family environment are significant effect to interest become a teacher. 3) Perception of students about the profession teacher and family environment jointly had a significant effect to interest become a teacher.Keyword: Perception, The Profession Of Teacher, Family Environment, Interset